Correlation between the Borg score, static disorders, and general symptomatology in patients with chronic dyspnea - Kinga Vindis; Ramona Nicoleta Suciu; Manuela Simona Pop; Mircea Gheorghe Pop; Cristina Aur; Diana Mocuta; Katalin Babeș; Carmen Pantis (Balneo and PRM Research Journal)
Chronic dyspnea, as a clinical symptom, may be present in several pulmonary diseases and cardiologic diseases, as well as anemia, loss of physical fitness, or anxiety. Any musculoskeletal disorder has a negative impact on the quality of life and adaptation to exertion, both of which are crucial for autonomy and reintegration into society, as well as for enhancing the quality of life of patients with chronic dyspnea. The objective of this study is to comparatively evaluate the demographic data, the symptomatology associated with chronic dyspnea, and the anthropometric data of the patients concerning the level of dyspnea assessed with the Borg scale, based on the hypothesis that the intensity of chronic dyspnea is associated with increasing age and with a higher number of comorbidities. We conducted a cross-sectional study from January 1, 2021, to June 30, 2022, which included 146 patients with chronic dyspnea of various causes, divided into three groups based on the Borg dyspnea score value. Data analysis suggests a higher prevalence of chronic dyspnea among men; more than 80% of patients in the Borg score 1 and 2 groups are younger than 60 years of age, while the majority of patients in Borg score 3 group (85.45%) are older than 61 years, with significant differences between groups. The number of associated diseases and musculoskeletal disorders is >3 in the Borg score 3 group. Increased dyspnea is associated with a higher number of comorbidities, including musculoskeletal disorders. Also, elderly patients with moderate dyspnea more frequently manifest associated clinical symptoms compared to those with mild dyspnea, thus highlighting the impact of dyspnea severity on overall health.